Comparative analysis of computing platforms for onboard micromodule of provisional image recognition - V. A. Kovalev; D. A. Paulenka; E. V. Snezhko; V. A. Liauchuk; A. A. Kalinovski (Informatika)
This paper is devoted to the analysis of basic hardware and software of recent cheap and commercially available computing microplatforms for selecting an appropriate solution for development of an onboard micromodule for preliminary recognition and selection of images of underlying surface of given types. It is assumed that the corresponding versions of the micromodule can be installed on board of small spacecraft or light unmanned aerial vehicles (drones). In this paper we consider a variant of a micromodule for drones. When choosing a microplatform, the main limitations were its low weight (no more than 300 g, including camera and interface equipment) and its relatively high performance (time for frame processing of a color image 320×240 pixels is no more than 300 ms). Another important limitation was the low price and commercial availability of microplatform on the Belarusian market. The information provided in this paper could be useful for engineers and researchers who are developing compact budget mobile systems for processing, analyzing and recognition of images.